Inverse correlation between freeze-thaw survival and storage stability of freeze-dried Lactobacillus reuteri DSM 17938 and a microcalorimetric search for GASP - Sawicki, Radoslaw (SLU/Department of Molecular Sciences, 2017)
Lactobacillus reuteri DSM 17938 is a probiotic bacterium manufactured by the company BioGaia AB and was in focus of this study. If a probiotic product is to confer its benefi-cial health effect to a consumer, it must retain high viability levels during long-term storage. A common practice for conservation of living microorganisms to meet this crite-rion is freeze-drying. Freeze-drying of bacteria is a process dependent on many factors and needs to be carefully designed in order to be successful. Preconditioning the bacteria before freeze-drying by subjecting them to different conditions during cultivation is one of the ways toward optimizing the survivability of freeze-drying and subsequent storage-stability. In theory, finding more robust mutants of L. reuteri could be yet another way of reaching this goal. It has been discovered that at least in some species of bacteria, in-creasingly resilient generations of mutants arise in consecutive waves during prolonged batch cultivation and are referred to as “growth advantage in stationary phase” (GASP) mutants. The overall goal of this study was to work towards a viable and storage-stable product based on L. reuteri. The first objective was to investigate if survival of a freeze-thaw assay, in which differently preconditioned L. reuteri are subjected to cycles of freezing and thawing, correlates with storage-stability. This could verify the potential use of the freeze-thaw assay instead of performing slow and laborious long-term stability studies when optimizing the production process, as well as provide insights into which cultiva-tion conditions confer the highest storage-stability. A second objective was to investigate prolonged batch cultures of L. reuteri as a hypothetical source of GASP mutants. It was further hypothesized that appearance of GASPs would be detectable by isothermal micro-calorimetry. L. reuteri was cultivated at different settings of pH and temperature and freeze-dried in a 15% w/v sucrose formulation. Survival of the freeze-thaw assay and an accelerated storage assay at 37 °C were compared by viable counting and subsequent ANOVA and Tukey’s test. This was complemented by microscopic morphology and Gram-stain stud-ies. For the mutant-related experimental objective, L. reuteri and E. coli (as a control organism) were cultivated for up to 70 days while their heat production was measured in isothermal microcalorimeters (IMC). A consistent inverse correlation was found between the freeze-thaw assay and the ac-celerated storage assay. High pH, and to a lesser extent, high temperature were associated with higher stability but lower freeze-thaw assay survival. Microscopic studies did not find any consistent association between stability and morphology except for the absence of cell clumps in the most storage-stable case. No GASP-revealing heat flows could be observed, neither with L. reuteri or E. coli controls. The collected data implied that L. reuteri did not produce GASP mutants. Future effort is suggested to be put into finding out if survival of the freeze-drying and subsequent storage-stability can both be improved independently and in such case, separate assays for both criteria should be employed. In conclusion, it is likely that the causes for differences in storage-stability and freeze-thaw survival reside in biomolecular phenomena affected by cultivation conditions. IMC does not seem to be a feasible tool for GASP detection; the possible reason could be lack of agitation and thereby no GASP growth. However, IMC devices with stirring could still be evaluated as a tool for GASP detection.